Anabolic agent use in adults with cystic fibrosis. (October 2015) - Green, Heather D.; Barry, Peter J.; Jones, Andrew M.
Summary: The use of non-prescribed anabolic agents amongst non-athletes is increasing with young, adult males with cystic fibrosis (CF) in the highest risk demographic. There is evidence that anabolic agents increase weight and muscle mass in adults with a variety of catabolic conditions but there is no evidence for their use in hormone sufficient adults with CF. We report a case of anabolic agent use in a male adult with CF and review the clinical features of anabolic agent use with a focus on adults with CF.